STUDENTS’ IMPROVED UNDERSTANDING OF LIMIT TRIGONOMETRIC FUNCTIONS THROUGH IMPLEMENTATION JIGSAW LEARNING - Dadang Sumianto (MATEMATIKA DAN PEMBELAJARAN, 2023)
This is a classroom action research is to achieve student success in learning mathematics, especially how to complete Trigonometry Function Limits by applying the Jigsaw learning model. The subjects in this study were students of class XII IPA 1 SMAN 1 Dawarblandong Mojokerto Regency in the 2022/2023 school year with a total of 36 students. The instruments in this study used syllabus, lesson plans, worksheets, observation sheets, and evaluation question sheets. The data analysis method uses 2 cycles with each cycle consisting of 5 stages namely preparation (planning), implementation (action), observation (observation), evaluation (evaluation), and reflection (reflection). The results showed that the jigsaw cooperative learning model had a positive impact on improving student achievement which was marked by an increase in student mastery in each cycle, namely cycle I 63.88% and cycle II 94.44%. The application of the Jigsaw cooperative learning method has a positive effect, namely increasing student learning motivation as indicated by the results of the second cycle test which are better than the first cycle test results and the results of observations of teachers and students.